Factors of Regional Economic and Social Systems Stability In the Post-Pandemic Period: Russian Experience - Alevtina Pavlovna SUVOROVA; Olga Mikhailovna REPINA; Natalia Yuryevna SUDAKOVA; Svetlana Alekseevna RUDENKO; Evgeny Alekseyevich IVANOV; Olga Viktorovna LITVINOVA; Marina Sergeevna ABROSIMOVA; Renata Vasilievna MIKHAILOVA (Communications of International Proceedings, 2021)
The developing new world economic order initiates deep contradictions in the proportions of the world economic and social system development. The Covid crisis has exacerbated the manifestations of these contradictions and made problems not only for a "new economy" formation, but also put at risk the recovery of the national economies in countries with emerging market and developing countries, as well as countries with a low economic development level.  The study of the Russian economy recovery experience during the post-pandemic period confirmed the insufficient efficiency of existing models and instruments of economic development under conditions of strong regional differentiation. The factors of external and internal environment that determine the stability of the regional social and economic system during the post-pandemic period are highlighted. This paper evaluates the stability of a selection totality of regional social and economic systems of the Russian Federation, taking into account their readiness for the Covid crisis, the degree of regional budget execution and pandemic risks level. The following types of regional social and economic systems (RSES) are identified: formalized, transitional, unformalized. The article observes the experience of the Russian RSES, which have shown stability under the conditions of Covid crisis, the factors that have provided an improvement in positions of these regions in the space of the national economy of the Russian Federation are presented.
Keywords: Covid crisis; countries with emerging markets and developing countries; regional social and economic system (RSES); typology and grouping of RSES by crisis tolerance; RSES stability evaluation; methodological tools.